A 1.3-mb 7q11.23 atypical deletion identified in a cohort of patients with williams-beuren syndrome - Delgado, L M (2013)
Fil: Delgado, L.M. ANLIS Dr. Carlos G. Malbrán. Centro Nacional de Genética Médica (CENAGEM); Argentina.